Figurations of Attachment in Sylvia Plath and Halina Poświatowska - Agnieszka Pantuchowicz (European Journal of American Studies)
The paper addresses the question of attachment to places and the modes of its reflection in the “periautobiographical” (James Olney’s term) texts of Sylvia Plath and Halina Poświatowska. For these two women writers the change of the place of living (from America to England in the case of Plath, and from Poland to America in the case of Halina Poświatowska) was a significant event which can be read as a history in which the topographical change becomes crucial for the construction of autobiographical memory. This memory, partly constituted by the play of attachments and detachments, is also crucial for the understanding of the role of the ideas of home and homeland seen as a refigured space of attachment in which the idea friendship and its various bonds are links with what is close to oneself, even if this closeness is felt as unwelcome and troublesome.